Paris polyphylla 26 triggers G2/M phase arrest and induces apoptosis in HepG2 cells via inhibition of the Akt signaling pathway. Issue 4 (April 2019) - Li, Qiang; He, Zifan; Liu, Jiming; Wu, Jianlong; Tan, Guixiang; Jiang, Jianwei; Su, Zexuan; Cao, Mingrong
Objectives: Paris polyphylla 26 (PP-26) is a monomer purified from Paris polyphylla, which has traditionally been used as an antimicrobial, hemostatic, and anticancer agent in China. The anti-proliferation effect and underlying molecular mechanism of PP-26 were investigated in vitro. Methods: The effects of PP-26 on various tumor cells were detected by MTT assay. PP-26-affected cell cycle and cell cycle-related proteins in HepG2 cells were detected by flow cytometry and western blotting, respectively. Apoptosis in response to PP-26 was assessed by Hoechst 33258 staining and flow cytometry. PP-26-affected apoptosis-related proteins and Akt signaling were detected by western blotting. The inhibitory effect of PP-26 on HepG2 cells, when combined with 5-fluorouracil (5-FU), was also assessed. Results: PP-26 inhibited proliferation of HepG2 cells in a dose-dependent manner by triggering G2/M-phase arrest. Moreover, PP-26 induced apoptosis of HepG2 cells. Expression levels of apoptosis proteins caspase 9, caspase 3, PARP, Bcl-2, Bcl-xL, and Mcl-1 were downregulated, while the expression level of apoptosis protein Bax was upregulated. Expression levels of p-Akt, p-GSK-3β, and p-Foxo3 were downregulated. Combination with PP-26 enhanced 5-FU inhibition of HepG2 cell proliferation. Conclusions: PP-26 triggers G2/M-phase arrest and induces apoptosis in HepG2 cells via inhibition of the Akt signaling pathway.